2007
DOI: 10.1021/jp075177v
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphonate Self-Assembled Monolayers for Gate Dielectric Surface Modification of Pentacene-Based Organic Thin-Film Transistors:  A Comparative Study

Abstract: Organic thin-film transistors using pentacene as the semiconductor were fabricated on silicon. A series of phosphonate-based self-assembled monolayers (SAMs) was used as a buffer between the silicon dioxide gate dielectric and the active pentacene channel region. Octadecylphosphonate, (quarterthiophene)phosphonate, and (9-anthracene)phosphonate SAMs were examined. Significant improvements in the sub-threshold slope and threshold voltage were observed for each SAM treatment as compared to control devices fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 32 publications
3
46
0
Order By: Relevance
“…In contrast, threshold voltage increased when using high-k materials such as Ta 2 O 5 , Si 3 N 4 and HfO 2 as shown in Figure 8(a). Some studies have shown that chemical modification using SAM or organic insulating materials on dielectric interfaces can induce low threshold voltage [15][16][17]. Klauk et al reported that positive threshold voltage was obtained using sputtered material [18].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, threshold voltage increased when using high-k materials such as Ta 2 O 5 , Si 3 N 4 and HfO 2 as shown in Figure 8(a). Some studies have shown that chemical modification using SAM or organic insulating materials on dielectric interfaces can induce low threshold voltage [15][16][17]. Klauk et al reported that positive threshold voltage was obtained using sputtered material [18].…”
Section: Resultsmentioning
confidence: 99%
“…[239][240][241][242][243][244][245][246][247][248] For example, Forrest and co-workers observed major TFT mobility and I on :I off enhancement when using OTS-treated gate dielectrics in P5 TFTs, from 0.06 cm 2 ) over other devices using octadecylsilane and other phosphonates. [250] In this study, a new (anthracene)phosphonate SAM was reported (Fig. 14C), and compared to the other [238] explained OTFT performance enhancements related to P5 grain size using the multiple trapping and release model.…”
mentioning
confidence: 82%
“…Molecular interaction with solid surfaces has attracted considerable attention in the scientific literature due its relevance to such areas as catalysis, 1 atmospheric pollution, 2 magnetic storage systems, 3 planetary science, 4 organic electronic materials, 5 soil contamination, 6 molecular information processing, 7 and geophysics. 8 Theoretical studies have often focused on model systems designed to explore adsorption of a single aliphatic or aromatic molecule.…”
Section: Introductionmentioning
confidence: 99%